Environmental Enrichment From Birth Impacts Parvalbumin Expressing Cells and Wisteria Floribunda Agglutinin Labelled Peri-Neuronal Nets Within the Developing Murine Striatum - Angela May O'Connor; Thomas Joseph Burton; Hannan Mansuri; Gabriel Rhys Hand; Catherine Anne Leamey; Atomu Sawatari (Frontiers Media S.A., 2019)
Environmental enrichment can dramatically affect both the development and function of neural circuits. This is accomplished, at least in part, by the regulation of inhibitory cellular networks and related extracellular matrix glycoprotein structures known as perineuronal nets. The degree to which enhanced housing can influence brain areas involved in the planning and execution of actions is not well known. We examined the effect of enriching mice from birth on parvalbumin expression and perineuronal net formation in developing and adult striatum. This input nucleus of the basal ganglia consists of topographically discernible regions that serve different functions, providing a means of simultaneously examining the influence of environmental factors on discrete, but related networks. Greater densities of striatal parvalbumin positive cells and wisteria floribunda agglutinin labelled perineuronal nets were present in enriched pups during the second postnatal week, primarily within the lateral portion of the nucleus. Housing conditions continued to have an impact into adulthood, with enriched mice exhibiting higher parvalbumin positive cell densities in both medial and lateral striatum. Curiously, no differences due to housing conditions were detected in striatal perineuronal net densities of mature animals. The degree of overlap between striatal parvalbumin expression and perineuronal net formation was also increased, suggesting that heightened neural activity associated with enrichment may have contributed to greater engagement of networks affiliated with cells that express the calcium binding protein. Brain derived neurotrophic factor, an important regulator of inhibitory network maturation, is also subtly, but significantly affected within the striatum of enriched cohorts. Together, these findings suggest that environmental enrichment can exert cell specific effects within different divisions of an area vital for the regulation of action.